The Promises and Pitfalls of Using Chat GPT for Self-Determined Learning in Higher Education: An Argumentative Review - Baskara, FX. Risang (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The potential of artificial intelligence language models, such as Chat GPT, to support self-determined learning in higher education has garnered increasing attention from educators, researchers, and policymakers. However, the promises and pitfalls of using Chat GPT for self-determined learning remain subject to debate and warrant further exploration. In this argumentative review, we examine the central questions and statements of the problem related to the use of Chat GPT for self-determined learning in higher education. We synthesise and critically evaluate the existing literature on the potential of Chat GPT to support self-directed and self-determined learning and highlight the main challenges and concerns associated with its use. According to our analysis, Chat GPT promises to improve self-determined learning by offering individualised feedback, resources, and assistance to learners that can foster their acquisition of knowledge and skills. However, using Chat GPT in self-determined learning also raises ethical and pragmatic concerns. These include issues about privacy, data security, and algorithmic bias, which could compromise the effectiveness and reliability of Chat GPT-based interventions. We posit that while the potential benefits of Chat GPT for self-determined learning are significant, they must be weighed against its potential drawbacks. As such, the design, implementation, and assessment of Chat GPT-based higher education interventions must be carefully considered. Our results indicate that the advancement of Chat GPT-based interventions for self-determined learning in higher education necessitates a nuanced and multidisciplinary approach that considers the viewpoints of educators, researchers, learners, and other interested stakeholders.